Ozone variations derived by a chemical transport model - Eleftheratos, K.; Isaksen, I.; Zerefos, C.; Nastos, P.; Tourpali, K.; Rognerud, B. (Water, Air, and Soil Pollution, 2013)
The results of a comparison between monthly mean ozone column variations calculated from the chemical transport model Oslo CTM2 and those derived from solar backscatter ultraviolet (SBUV) satellite observations are presented for the period 1998-2009. Monthly mean total ozone derived from improved model simulations were used to compute monthly zonal means over 10 latitude zones over the northern and southern hemispheres. Ozone column variations from Oslo CTM2 are highly correlated with SBUV retrievals at all latitude zones. Equatorial zonal winds at 30 hPa were used as index to study the impact of quasi-biennial oscillation (QBO) on ozone. Correlations between modeled ozone and the QBO were found to be the order of +0.8 in the tropics. The impact of QBO was most pronounced at equatorial latitudes with amplitudes of +4 to -4 %. Seasonal variations in surface ozone and tropospheric ozone column calculated by the model are also presented. © 2013 Springer Science+Business Media Dordrecht.
Keywords: analytic method; article; Atmospheric chemistry; atmospheric modeling; Atmospheric pressure; atmospheric transport; chemical reaction; chemical transport model; Chemical transport models; computer simulation; correlation analysis; environmental impact; environmental parameters; latitude; Northern Hemisphere; oscillation; Oslo CTM2; Ozone; Ozone layer; QBO; quasi biennial oscillation; Quasi-biennial oscillation; Satellite observations; SBUV; seasonal variation; Southern Hemisphere; ultraviolet radiation; Variations; zonal wind